2007
DOI: 10.1038/sj.npp.1301646
|View full text |Cite
|
Sign up to set email alerts
|

N-Desalkylquetiapine, a Potent Norepinephrine Reuptake Inhibitor and Partial 5-HT1A Agonist, as a Putative Mediator of Quetiapine's Antidepressant Activity

Abstract: Quetiapine is an atypical antipsychotic drug that is also US FDA approved for treating bipolar depression, albeit by an unknown mechanism. To discover the potential mechanism for this apparently unique action, we screened quetiapine, its metabolite N-Desalkylquetiapine, and dibenzo [b,f][1,4]thiazepine-11(10-H)-one (DBTO) against a large panel of G-protein-coupled receptors, ion channels, and neurotransmitter transporters. DBTO was inactive at all tested molecular targets. N-Desalkylquetiapine had a high affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
222
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(230 citation statements)
references
References 43 publications
(54 reference statements)
4
222
1
3
Order By: Relevance
“…Despite extensive research, the etiology of pain in fibromyalgia remains elusive, although central sensitization has emerged as a leading theory explaining the mechanism of disease (10). The analgesic effects of quetiapine XR may be mediated in part by its dopaminergic actions as well as its effects on both the serotonergic and noradrenergic systems (24,25,30). Our study is the first to show that quetiapine XR significantly improves measures of depression and pain in patients with a dual diagnosis of MDD and fibromyalgia and may therefore constitute a rational choice to target both conditions concurrently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite extensive research, the etiology of pain in fibromyalgia remains elusive, although central sensitization has emerged as a leading theory explaining the mechanism of disease (10). The analgesic effects of quetiapine XR may be mediated in part by its dopaminergic actions as well as its effects on both the serotonergic and noradrenergic systems (24,25,30). Our study is the first to show that quetiapine XR significantly improves measures of depression and pain in patients with a dual diagnosis of MDD and fibromyalgia and may therefore constitute a rational choice to target both conditions concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that the parent compound, quetiapine fumarate, is a partial agonist at serotonin receptor 1A (5-HT 1A ) and an antagonist at 5-HT 2A and 5-HT 3A , D 1 and D 2 dopamine receptors, H 1 histamine receptor, and ␣ 1 -and ␣ 2 -adrenergic receptors (24). Furthermore, one of its major metabolites, norquetiapine, has been shown to have a moderate affinity for the norepinephrine reuptake transporter and a 10-fold more potent effect than quetiapine at 5-HT 1A (25). This receptor-binding profile likely explains the demonstrated antidepressant efficacy of quetiapine XR as monotherapy for the treatment of both bipolar (26) and unipolar depression (27)(28)(29).…”
mentioning
confidence: 99%
“…4,9,[39][40][41][42] Norquetiapine, the major metabolite of quetiapine, is anticholinergic and can produce blurred vision and dry mouth among other anticholinergic side effects. 9,14 Relevant to its use to treat anxiety and insomnia, quetiapine has been repeatedly associated with withdrawal reactions as well as abuse and dependence. 43,44 In addition to concerns over the use of quetiapine in treating patients with major depression, anxiety or sleep problems, we have concerns about inadequate monitoring of patients of all ages who are taking quetiapine and other antipsychotics.…”
Section: Cmaj Openmentioning
confidence: 99%
“…Ketiapinin major depresyon üzerindeki etkisinin, aktif metaboliti olan norketiapinin rolü olduğu ve bu etkiyi noradrenalin taşıyıcısı (NET) üzerindeki antagonist etkisiyle ilişkili olduğu düşünülmektedir (35)(36)(37). Ketiapin XR kararlı durumdayken PET ile NET'in değerlendirildiği sağlıklı gönüllülerde, NET'in aktivitesinde azalma saptanmıştır (38).…”
Section: Ketiapin (Xr) ıN Farmakodinamiği; Klinik Sonuçlarıunclassified